Chronic ethanol consumption increases dopamine uptake in the nucleus accumbens of high alcohol drinking rats - Carroll, Michelle R. (2006)
Past research has indicated that chronic ethanol exposure enhances dopamine (DA) neurotransmission in several brain regions. The present study examined the effects of chronic ethanol drinking on dopamine transporter (DAT) function in the nucleus accumbens (Acb) of High-Alcohol-Drinking replicate line 1 (HAD-1) rats. HAD rats were given concurrent 24-hr access to 15% ethanol and water or water alone for 8 weeks. Subsequently, DA uptake and the V(max) of the DAT were compared between the two groups using homogenates of the nucleus accumbens. DA uptake was measured following a 2 minute incubation at 37°C in the presence of 8 nM [(3)H]DA. For kinetic analyses, DA uptake was assessed in the presence of 5 concentrations of [(3)H]DA ranging from 8nM to 500nM. Analyses of the data revealed a significant increase in DA uptake in the ethanol group compared to water controls. Kinetic analyses revealed the change in DA uptake to be a consequence of an increase in the V(max) of transport. These findings demonstrate that chronic free-choice oral ethanol consumption in HAD-1 female rats increases DA uptake in the Acb by increasing the V(max) of the transporter. However, it is not known whether the ethanol-induced change in V(max) is caused by differences in the actual number of available transporter sites or from a difference in the velocity of operation of a similar number of transporters. Overall, the data indicate that chronic ethanol consumption by HAD-1 rats produces prolonged neuroadaptations within the mesolimbic DA system, which may be important for the understanding of the neurobiological basis of alcoholism.